Surgery or Non-surgical Treatment of ≤8 mm Non-small Cell Lung Cancer: A Population-Based Study - Shen, Jianfei; Zhuang, Weitao; Xu, Congcong; Jin, Ke; Chen, Baofu; Tian, Dan; Hiley, Crispin; Onishi, Hiroshi; Zhu, Chengchu; Qiao, Guibin (Frontiers in Surgery, 2021)
Background: Timing for intervention of small indeterminate pulmonary nodules has long been a topic of debate given the low incidence of malignancy and difficulty in obtaining a definite preoperative diagnosis. We sought to determine survival outcomes of surgical and non-surgical managements in non-small cell lung cancer (NSCLC) ≤ 8mm, which may provide a reference for prospective decision-making for patients with suspected NSCLC. Method: A total of 1,652 patients with Stage IA NSCLC ≤ 8mm were identified from the Surveillance, Epidemiology, and End Results (SEER) database and categorized into surgery and non-surgery groups. Chi-square test, t-test and Mann-Whitney U test were used to compare the baseline characteristics between groups. Survival curves was depicted using Kaplan-Meier method and compared by log-rank test. Cox proportional hazard model was used for univariate and multivariate analyses. Adjustment of confounding factors between groups was performed by propensity score matching. Results: The surgery and non-surgery groups included 1,438 and 208 patients, respectively. Patients in surgery group demonstrated superior survival outcome than patients in non-surgery group both before [overall survival (OS): HR, 16.22; 95% CI, 11.48-22.91, p < 0.001; cancer-specific survival (CSS): HR, 49.6; 95% CI, 31.09-79.11, p < 0.001] and after (OS: HR, 3.12; 95% CI, 2.40-4.05, p < 0.001; CSS: HR, 3.85; 95% CI, 2.74-5.40, p < 0.001) propensity score matching. The 30-day mortality rates were 3.1% and 12.0% in surgery and non-surgery groups, respectively. Multivariate analysis suggested age, sex, race, tumor size, grade, pathological stage were all independent prognostic factors in patients with ≤ 8mm NSCLC. A comparison of surgical resections revealed a survival superiority of lobectomy over sub-lobectomy. In terms of CSS, no statistically significant difference was found between segmentectomy and wedge resection. Conclusion: The current SEER database showed better prognosis of surgical resection than non-surgical treatment in patients with ≤ 8mm NSCLC in SEER database, but the factors that should be essentially included in the proper propensity-matched analysis, such as comorbidity, cardiopulmonary function and performance status were unavailable and the true superiority or inferiority should be examined further by ongoing randomized trial especially comparing surgery and stereotactic body irradiation.